2020
DOI: 10.3390/ijerph17041275
|View full text |Cite
|
Sign up to set email alerts
|

Can Age-Friendly Planning Promote Equity in Community Health Across the Rural-Urban Divide in the US?

Abstract: In the US, rural communities face challenges to meet the community health needs of older adults and children. Meanwhile, rural areas lag in age-friendly built environment and services. AARP, a US based organization promoting livability for all ages, has developed a Livability Index based on the World Health Organization’s (WHO) domains of age-friendly communities: health, housing, neighborhood, transportation, environment, engagement, and opportunity. This study links the 2018 AARP Livability Index categories … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
29
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 29 publications
(30 citation statements)
references
References 46 publications
0
29
1
Order By: Relevance
“…Our second research question explores the role of planning and social inclusion on child-friendly zoning codes and services. While prior studies have identified the critical role of engagement of families with children and youth in promoting community health [ 3 , 19 , 39 , 42 , 49 ], our results show that a common vision across generations, race, and ethnicity is as important as engagement in building healthy communities for children. Positive attitudes toward families with children are not enough.…”
Section: Discussioncontrasting
confidence: 74%
See 2 more Smart Citations
“…Our second research question explores the role of planning and social inclusion on child-friendly zoning codes and services. While prior studies have identified the critical role of engagement of families with children and youth in promoting community health [ 3 , 19 , 39 , 42 , 49 ], our results show that a common vision across generations, race, and ethnicity is as important as engagement in building healthy communities for children. Positive attitudes toward families with children are not enough.…”
Section: Discussioncontrasting
confidence: 74%
“…Public health agencies such as the Robert Wood Johnson Foundation and the National Institutes for Health Disparities recognize the importance of engagement and inclusion in meeting the needs of children [ 10 , 11 ]. Cross-agency collaboration, local government policy and social inclusion are recognized as key community level factors determining public health outcomes [ 39 , 41 ]. Planners have an especially important role in promoting child health in both rural and urban settings [ 45 , 46 , 47 ].…”
Section: Literature Reviewmentioning
confidence: 99%
See 1 more Smart Citation
“…However, up to September 2020, 14 out of 50 states in the US still did not mandate mask wearing in public [ 31 ]. The lifting of shutdown orders and the rapid move to reopening disproportionally affected the minority population, as a higher percentage of minorities work in low-paid essential occupations [ 2 , 32 ], and minority communities have less access to health care and prevention, and a low quality of health care generally [ 33 , 34 ]. Due to inequities in the social determinants of health among minority groups, the infection rate among minorities is almost three times the infection rate of whites [ 35 ].…”
Section: Introductionmentioning
confidence: 99%
“…In the city model, we control for community health, using the health category in the AARP livability index (2018). This is measured at the county level and has been used in other studies of public health ( Zhang et al, 2020 ). The health category is an index on a scale of 0–100, which captures prevention, access, and quality at the county level.…”
Section: Introductionmentioning
confidence: 99%